Uso de la internet y su impacto en la producción de textos en los alumnos de IX y X ciclo de la carrera profesional de Educación primaria de la FEH – R - Mori Vargas, Géssler (2011)
The purpose of this investigation is to determine the influence of the internet in the production of texts in the students of IX and X to cycle and humanities faculty of education, elementary education career in 201 O Rioja district The research is descriptive, eta study population consists of 24 students in the nínth and tenth cycle of the faculty of education and humanities, primary education career in 201 O Rioja district. For data collection technique was applied to survey items that were administered to students to obtain data on how internet use affects the production of their texts:f: Data processing was used descriptive statistics to obtain the mean, coefficient of variation. Thus, the study says the alternative hypothesis and rejects the null hypothesis, confirming that the use of Internet influences the production of texts for students of IX and X of the career cycle of primary education FEH-R In relation to the research results found that among Internet use and each dimension of the production of texts, obtained by the students of IX and X of the career cycle of primary education. In this sense, Internet use correlated with the planning and drafting, it showed a significant positive correlation. And to make the correlation in the use of the internet with the review, showed a positive correlation average. Meaning that text production is being influenced by 62.16% with the use of internet, this indicates that 37.84% is influenced by other factors.